TINJAUAN HUKUM ISLAM TERHADAP SANKSI ADAT KAWIN SUMBONG DI MASYARAKAT LEKUK 50 TUMBI LEMPUR - Fajri, Yan; Eva, Yusnita; Puspita, Mega (UIN Imam Bonjol Padang, 2021)
This research is motivated by the marriage between a niece and her uncle known as sumbong marriage. The uncle in question is not the mother's biological sister, but the mother's distant relative. In Islamic law, there is no prohibition against this kind of marriage. Based on the customary law of Lekuk 50 Tumbi Lempur, the marriage has violated customary provisions and is subject to sanctions, namely by paying one goat. The research method used is descriptive qualitative by processing data with sentences or words and going directly to the field for interviews. The results of this study indicate that: First, this customary sanction has been passed down from generation to generation. There are several reasons for the imposition of sanctions, namely to expand kinship relations, strengthen kinship ties and maintain offspring because it originated from an endogamous marriage system. Second, the consequences of sanctions, namely for people who violate customary provisions, will be punished, both materially and morally. Materially, that is by paying for one goat, while morally it will be excommunicated, excluded from various traditional activities and considered to have violated customary provisions. Third, if viewed from the perspective of Islamic law, the sanction of celibate marriage is only a habit factor for the people of Lekuk 50 Tumbi Lempur and does not conflict at all with Islamic law in principle. The imposition of sanctions turned out to have a positive impact, among others: expanding kinship relations, maintaining brotherly ties and maintaining offspring.